Case report: A late and isolated presentation of meningoencephalomyelitis uncovers a novel pathogenic variant in the CIITA gene - Alosaimi, Mohammed F.; Hamad, Muddathir H.; AlShammari, Muneera J.; Jamjoom, Dima Z.; Musibeeh, Najd S. (Frontiers in Pediatrics, 2023)
Background Bare lymphocyte syndrome type II (BLS II) is a rare form of severe combined immunodeficiency caused by mutations in the CIITA gene, which regulates major histocompatibility complex class II (MHC II) expression. Objective We report the case of a Saudi boy with a novel mutation in the CIITA gene who presented with acute and late meningoencephalomyelitis, resulting in severe neurodevelopmental regression. Methods We reviewed the patient's clinical and laboratory data obtained from medical records and performed a literature search on BLS II. Results The patient presented with acute meningoencephalomyelitis confirmed by MRI findings and was later found to carry a homozygous pathogenic variant in the CIITA gene p.(Leu473Hisfs*15). The patient had no MCH II expression, confirming the genetic diagnosis of autosomal recessive BLS II. Surprisingly, the patient's prior clinical history was unremarkable for significant infections or autoimmunity. Conclusions We report a case with a novel CIITA gene mutation presenting atypically with a late and isolated severe infection. Isolated severe meningoencephalomyelitis may be a manifestation of primary immunodeficiency.